2015
DOI: 10.1097/dss.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Microscopic Excision of a Subungual Glomus Tumor

Abstract: Microscopic surgical excision enables the surgeon to completely remove a glomus tumor while minimizing damage to the nail unit, thereby resulting in significantly decreased recurrence and nail deformity. In this study, an incision made according to the anatomic location provided an easy approach and the best visualization. Patients' finger function was successfully restored, nail esthetic outcome was good, and patient satisfaction was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Meticulous dissection using magnification is reported to be helpful for complete tumour removal. Huang et al (2015), performed transungual and lateral subungual approaches to excise subungual glomus tumours in 22 cases. The study reported no recurrences or nail deformities within the mean follow-up of 48 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meticulous dissection using magnification is reported to be helpful for complete tumour removal. Huang et al (2015), performed transungual and lateral subungual approaches to excise subungual glomus tumours in 22 cases. The study reported no recurrences or nail deformities within the mean follow-up of 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the subperiosteal approach can preserve the nail unit, decreasing nail deformities. However, this approach cannot effectively expose centrally located tumours and is more effective for laterally located tumours (Huang et al., 2015). The nail-sparing approach elevates a portion of the nail and restores it after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although glomus tumours are usually well encapsulated and easily enucleated, additional aids, such as the microscope (Huang et al., 2015; Lee et al., 2009; Muramatsu et al., 2014; Wang et al., 2013) or surgical loupes (Hufschmidt et al., 2017; Kim et al., 2018), optimize complete resection and help to distinguish pulp lesions from fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The former allows good exposure and the latter avoids injuring the nail bed and having to reconstruct it. Huang et al. (2015) advocate that subperiosteal approaches cannot expose centrally located tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the tumor is performed in a bloodless field, with tourniquet application, under loupe magnification [11]. A bloody field can preclude complete excision and lead to recurrence [12].…”
Section: Introductionmentioning
confidence: 99%